Detailed Analysis of the Crystal Structures and Magnetic Properties of a Dysprosium(III) Phthalocyaninato Sextuple‐Decker Complex: Weak f–f Interactions Suppress Magnetic Relaxation. Issue 12 (4th February 2019) - Horii, Yoji; Katoh, Keiichi; Sugimoto, Kunihisa; Nakanishi, Ryo; Breedlove, Brian K.; Yamashita, Masahiro
Abstract: In the research field of single‐molecule magnets (SMMs), lanthanoid–lanthanoid interactions, so‐called f–f interactions, are known to affect the SMM properties, although their magnitudes are small. In this article, an SMM with very weak f–f interactions is reported, and the effects of the interactions on the SMM properties are discussed. X‐ray structural analysis of the Dy III ‐Cd II ‐phthalocyaninato sextuple‐decker complex (Dy2 Cd3 ) reveals that the intramolecular Dy−Dy length in Dy2 Cd3 is more than 13 Å, which is longer than the intermolecular Dy−Dy length. Even though the two Dy III ions are far apart, intermolecular ferromagnetic dipole–dipole interactions are observed in Dy2 Cd3 . From detailed analysis of ac magnetic susceptibilities, quantum tunneling of the magnetization (QTM) in Dy2 Cd3 is partially suppressed owing to the existence of very weak Dy−Dy interactions. Our results show that even very weak Dy−Dy interactions act as a dipolar bias, suppressing QTM. Abstract : Single‐molecule magnets : The crystal structures and magnetic properties of a dysprosium(III) phthalocyaninato sextuple‐decker complex (see figure) are determined for the first time. Although two dysprosium(III) ions in the sextuple‐decker complex are distant from each other, very weak magnetic interactions between them have a significant impact on the single‐molecule magnet properties.